Educational and Gender Differences in Health Behavior Changes After a Gateway Diagnosis - Hernandez, Elaine M. (J Aging Health, 2016)
OBJECTIVE: Hypertension represents a gateway diagnosis to more serious health problems that occur as people age. We examine educational differences in three health behavior changes people often make after receiving this diagnosis in middle or older age, and test whether these educational differences depend on (a) the complexity of the health behavior change and (b) gender. METHOD: We use data from the Health and Retirement Study and conduct logistic regression analysis to examine the likelihood of modifying health behaviors post diagnosis. RESULTS: We find educational differences in three behavior changes—antihypertensive medication use, smoking cessation, and physical activity initiation—after a hypertension diagnosis. These educational differences in health behaviors were stronger among women compared with men. DISCUSSION: Upon receiving a hypertension diagnosis, education is a more important predictor of behavior changes for women compared with men, which may help explain gender differences in the socioeconomic gradient in health in the United States.